Contrasting Responses of Pyrido[2,1-a]isoindol-6-ones and Their Sultam Counterparts to Photochemical Activation - Paquette, Leo A; Dura, Robert D; Modolo, Isabelle (Journal of organic chemistry, 2009)
A ring-closing metathesis-based strategy has allowed access to an unreported pair of pyridoisoindolones and their previously unknown sultam counterparts. The synthetic routing takes advantage of the ready availability of N-allylphthalimide and N-allylsaccharin and proceeds via the proper incorporation of small side chains into the heterocyclic ring. Positionally selective introduction of the conjugated diene functionality was realized efficiently. Detailed study of the excited-state chemistry of 7 and 8 showed both lactams to be subject to [4 + 2] dimerization under acetone-sensitized conditions. Different regioselectivities are involved, with the response of 8 being far more efficient than that exhibited by 7. No dimers could be isolated from the photolyzates of 9 and 10 under any conditions. While the latter sultam undergoes extensive polymerization, 9 is transformed via direct irradiation at 350 nm into 46 and 47 via [1,3]-sigmatropy involving the S−N bond and heterocyclic ring cleavage, respectively.